What my bias meant for my embodiment: an investigation on virtual embodiment in desktop-based virtual reality - You, Christopher; Peck, Tabitha; Stuart, Jacob; Gomes de Siqueira, Alexandre; Lok, Benjamin (Frontiers in Virtual Reality, 2024)
The immersion of VR can impact user perceptions in numerous forms, even racial bias and embodied experiences. These effects are often limited to HMDs and other immersive technologies that may not be inclusive to a general population. This paper investigates racial bias and embodiment on a less immersive but more accessible medium: desktop VR. A population of (n = 158) participated in a desktop simulation where they embodied a virtual avatar and interacted with virtual humans to determine if desktop embodiment is induced and if there is a resulting effect on racial bias. Our results indicate that desktop embodiment can be induced at low levels as measured by an embodiment questionnaire. Furthermore, one's implicit bias may actually influence embodiment, and the experience and perceptions of a desktop VR simulation can be improved through embodied avatars. We discuss these findings and their implications in the context of stereotype activation and existing literature in embodiment.